Three Food-Vessel Urns, a Cup-Marked Stone, and Other Objects discovered at Sheriffton, near Perth (Proceedings of the Society of Antiquaries of Scotland, 1918)
Three urns were buried together and two of them appear to have had sandstone lids. Fragments of cremated bone adhered to some of the sherds. A large flat stone nearby had four cups and a chiselled groove. An unusual structure of small sandstone pieces may have been a cist but the nature of its construction is not typical and it was empty. A block of sandstone was scored by a number of grooves cut by a chisel. Its date and function is unclear.